The Structure and Integration of the European Buyout Industry - Peter Cornelius (Vierteljahrshefte zur Wirtschaftsforschung, 2017)
The European private equity market has expanded meaningfully over the past few decades, with leveraged buyouts having averaged more than 50 billion euros per year in 2010–2016.This paper examines investment flows within Europe, as well as between Europe and the rest of the world at two levels: commitments from investors to private equity funds and acquisitions of portfolio companies by these funds. Although standard indicators of market integration are not available, these flows suggest that the European private equity market is significantly integrated both regionally and globally, with the United Kingdom serving as Europe's major hub. At the same time, the paper finds that financial intermediation in the European buyout industry has remained relatively fragmented, which has important implications for constructing institutional investors' portfolios. – – Der europäische Markt für Finanzbeteiligungen ist in den letzten Jahrzehnten stark expandiert. In den Jahren 2010–2016 betrug das Marktvolumen durchschnittlich mehr als 50 Milliarden Euro im Jahr. Dieser Artikel untersucht Kapitalflüsse innerhalb Europas als auch zwischen Europa und dem Rest der Welt. Dabei wird zwischen zwei Ebenen unterschieden, nämlich einerseits der Bereitstellung von Kapital an Private Equity Fonds durch institutionelle Investoren und andererseits der Verwendung von zugeflossenen Mitteln durch diese Fonds. Diese Kapitalflüsse deuten darauf hin, dass der europäische Markt für Finanzbeteiligungen ein hohes Mass an Integration aufweist, wobei dem Vereinigten Königreich eine Drehscheibenfunktion zukommt. Gleichzeitig scheint die europäische Fondsindustrie relativ fragmentiert zu sein, was erhebliche Konsequenzen für die Konstruktion von Portfeuilles haben könnte.
Keywords: F21; F36; G15; G24; G34; 330; Private equity; capital flows; portfolio investments; integration; market structure